2005
DOI: 10.1124/jpet.104.079343
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Interleukin-4 Effects on Calcium Signaling in Airway Smooth Muscle Cells

Abstract: In airway smooth muscle cells, interleukin (IL)-4 inhibited both carbachol-and caffeine-induced calcium mobilization from the sarcoplasmic reticulum (SR). Because of the known signaling pathways for IL-4 and importance of calcium uptake in maintaining SR calcium stores shared by agonists and caffeine, it was hypothesized that this rapid inhibitory effect might depend on phosphatidylinositol 3-kinase (PI3K) and on inhibition of calcium uptake by the SR. Enzyme-dispersed bovine trachealis cells were loaded with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
(55 reference statements)
2
8
0
Order By: Relevance
“…Theoretically, IL‐4 could decrease calcium in the SR by inhibiting calcium uptake via SERCA and/or by stimulating the release of calcium from the SR. In a prior study of these same cells, IL‐4 inhibited calcium transients in response to carbachol, even in the presence of a high concentration of CPA (30 μM), an inhibitor of SERCA (22). This finding suggested that IL‐4 did not decrease SR calcium content by inhibiting calcium uptake and, therefore, must be increasing the rate of release of calcium from the SR.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Theoretically, IL‐4 could decrease calcium in the SR by inhibiting calcium uptake via SERCA and/or by stimulating the release of calcium from the SR. In a prior study of these same cells, IL‐4 inhibited calcium transients in response to carbachol, even in the presence of a high concentration of CPA (30 μM), an inhibitor of SERCA (22). This finding suggested that IL‐4 did not decrease SR calcium content by inhibiting calcium uptake and, therefore, must be increasing the rate of release of calcium from the SR.…”
Section: Discussionmentioning
confidence: 82%
“…A prior study showed that the phosphatidylinositol 3‐kinase (PI3K) antagonists wortmannin and deguelin both inhibited the effect of IL‐4 on calcium transients (22). Because the current experiments showed that IL‐4 causes a net loss of SR calcium by mechanisms dependent on RyR calcium release channels, the simplest explanation or model for our findings is that IL‐4 stimulates signaling pathways involving PI3K to increase the release of calcium through RyR, thereby causing a net loss of calcium from the SR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite such progress, the mechanisms that underlie spontaneous tone in inflammatory bronchoconstriction and alterations in the phenotype of smooth muscle cells that accompany airway inflammation remain unknown. In asthma, evidence suggests that intrinsic alterations in ASM excitation-contraction coupling exist as compared with tissue from healthy subjects (18)(19)(20)(21)(22). Greater focus on the role of intracellular calcium release channels, the importance of the mechanisms of calcium sensitization, and changes of expression of ion channels, receptors, and second messengers is needed in physiologically relevant preparations and in human tissue.…”
Section: Excitation-contraction Couplingmentioning
confidence: 99%